The impact of task-based activities in reading skill for the students during covid 19 pandemic - Styati, Erlik Widiyani; Khasanah, Robingatun (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to investigate the impact of using task-based activities in reading skill for the eight students of junior high school of SMPN 4 MDN. Quantitative research was employed in this research. It was quasi experimental research design which used pre-test – post-test control group design. The population of this research were the eighth grade students of SMPN 4 MDN. The samples of this research were 8B as experimental class and 8C as control class. The sample was taken by using random sampling. In collecting the data, the researchers used reading test. The researcher used independent t-test on SPSS version 21 to analyze data. The results shows that the students who are treated by using task-based activities are more effective than the students who are treated by using conventional teaching. It means that teaching reading by using task-based activities gives a better influence on students’ reading skill. HIGHLIGHTS: Task-based learning affects how students acquire good informational reading skills both during and after the COVID-19 pandemic outbreak. Students in the experimental group learn more than students in the control group. During the tasks, students have the opportunity to share their knowledge about the topic, as well as exchange ideas and information.